A Run-time System for Efficient Execution of Scientific Workflows on Distributed Environments - Teodoro, George; Tavares, Tulio; Ferreira, Renato; Kurc, Tahsin; Meira, Wagner; Guedes, Dorgival; Pan, Tony; Saltz, Joel (International journal of parallel programming, 2008)
Scientific workflow systems have been introduced in response to the demand of researchers from several domains of science who need to process and analyze increasingly larger datasets. The design of these systems is largely based on the observation that data analysis applications can be composed as pipelines or networks of computations on data. In this work, we present a run-time support system that is designed to facilitate this type of computation in distributed computing environments. Our system is optimized for data-intensive workflows, in which efficient management and retrieval of data, coordination of data processing and data movement, and check-pointing of intermediate results are critical and challenging issues. Experimental evaluation of our system shows that linear speedups can be achieved for sophisticated applications, which are implemented as a network of multiple data processing components.